2021
DOI: 10.13057/biodiv/d220212
|View full text |Cite
|
Sign up to set email alerts
|

Morphotype diversity of Prorocentrum lima in the western part of Indonesian waters

Abstract: Abstract. Widiarti R, Zamani NP, Bengen DG, Madduppa H. 2021. Morphotype diversity of Prorocentrum lima in the western part of Indonesian waters. Biodiversitas 22: 609-616. Prorocentrum lima is one of the toxic benthic dinoflagellates, known to produce various toxins, including okadaic acid and dinophysis toxins. The species have a wide range of morphological variability, and possess morphotype diversity, which makes it essential to have detailed morphology observation for identification and other purposes. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, cells of isolate ISOP15 were characterized by smaller sizes as compared to other existing strains (20. 45 [34]. The phylogenetic analyses of the LSU rDNA (D1⁄D2) region showed the intermixing of Prorocentrum rhathymum and Prorocentrum mexicanum strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cells of isolate ISOP15 were characterized by smaller sizes as compared to other existing strains (20. 45 [34]. The phylogenetic analyses of the LSU rDNA (D1⁄D2) region showed the intermixing of Prorocentrum rhathymum and Prorocentrum mexicanum strains.…”
Section: Discussionmentioning
confidence: 99%
“…Prorocentrum lima is largely distributed from temperate to tropical marine areas worldwide [20,28,31]. Past studies indicated the cell shape, as expressed from the length/width ratio, of P. lima species as widely variable with ovoid, ellipsoid-oblong, ovate-oblong (oval-oblong), ovate-piriform, and round [13,20,21,23,28,33,37,38,[40][41][42][43][44][45]. Though early observations suggested that morphological gradations in cell size and shape within and between sites were minimal and not significant for P. lima [40,46]; however, it is now regarded as a "P. lima complex" [20,28,33].…”
Section: Discussionmentioning
confidence: 99%